2019
DOI: 10.1111/tbed.13437
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis trends in China, 2007–2018: A retrospective observational study

Abstract: Leptospirosis is one of the most common and neglected tropical waterborne diseases in China, causing serious economic losses, and constituting a significant public health threat. Leptospirosis has recently received increased attention and is considered a reemerging infectious disease in many countries. The incidence of leptospirosis among people suggests that occupation, age, season, sex and water recreational activities are significant risk factors. The aim of this study was to describe the epidemiological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…The fact that most cases were reported in an urban area and/or in a home environment corroborates results observed in numerous Brazilian studies [6][7][8][9][10][11][12][13][14][15][16]17,19,[35][36][37][38][39] . In addition, the most frequent exposures-involving water, flood mud and the presence of synanthropic rodentswere also reported in studies carried out in developing countries 16,17,40 .…”
Section: Discussionsupporting
confidence: 85%
“…The fact that most cases were reported in an urban area and/or in a home environment corroborates results observed in numerous Brazilian studies [6][7][8][9][10][11][12][13][14][15][16]17,19,[35][36][37][38][39] . In addition, the most frequent exposures-involving water, flood mud and the presence of synanthropic rodentswere also reported in studies carried out in developing countries 16,17,40 .…”
Section: Discussionsupporting
confidence: 85%
“…As a consequence, leptospirosis is a common and widespread zoonotic disease in China [ 11 , 12 ]. Although historically Guangdong province has had a relatively high incidence of human leptospirosis, in recent years, the disease has been only sporadically prevalent in this region [ 12 , 13 , 14 ]. However, limited information is available regarding the epidemiology of pathogenic Leptospira in wild rodents, which are the most important natural reservoirs for this pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the national surveillance system and prevention and control programs, improved housing, better waste management, and the improvement of agricultural mechanization, the average annual incidence of human leptospirosis in China has dramatically decreased [ 13 ]. A recent study indicated that for the past decade, human leptospirosis in China was primarily distributed in central-southern China, including the Guangdong province [ 14 ]. According to data available from the official departments of mainland China, the total number of confirmed leptospirosis cases nationwide was 297 in 2020, of which 23 cases were reported in the Guangdong province ( , accessed on 12 March 2021; , accessed on 19 February 2021).…”
Section: Introductionmentioning
confidence: 99%
“…So far, more than 80% of the provinces in China have reported leptospirosis cases, with a total of more than 2.5 million cases reported, including 20,000 deaths ( 73 ). Although the overall incidence of leptospirosis had shown a slow downward trend in recent years, there has also been an upward trend in some provinces of China (such as Fujian and Yunnan) ( 74 ). Murine have been the main source of infection, and livestock, especially pigs and cattle, and dogs are important hosts and sources of Leptospira ( 3 ).…”
Section: Discussionmentioning
confidence: 99%